Selection and validation of reference genes for quantitative real-time PCR in Rosmarinus officinalis L. in various tissues and under elicitation. (July 2019) - Aminfar, Zahra; Rabiei, Babak; Tohidfar, Masoud; Mirjalili, Mohammad Hossein
Abstract: The data normalization is a major subject in studies on the gene expression by quantitative polymerase chain reaction (qPCR) to ensure the reliability of obtained results. The normalization aims to remove variation sources with non-biological origins at the highest possible level. The accurate expression analysis greatly relies on the utilization of stable reference gene as an internal control for data normalization because expression patterns of these genes considerably alter across various kinds of tissue or within individual experimental conditions. However, little information is available on the stable reference genes in Rosmarinus officinalis L. The present study selected seven genes from the frequently-used housekeeping genes as candidate reference genes including Elongation factor1-alpha ( EF1-α ), 18S ribosomal RNA ( 18S rRNA ), Actin ( ACT ), alpha-Tubulin ( α-TUB ), Glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ), Cyclophilin ( CYP ), and beta-Tubulin ( β-TUB ). Four widely-used statistical algorithms, called NormFinder, geNorm, RefFinder, and BestKeeper, were utilized to evaluate the stability of expressing candidate reference genes in different types of tissue (callus, leaf, flower, stem, and root) and under the elicitor treatment (salicylic acid and methyl jasmonate). According to comprehensive results, GAPDH and 18S rRNA were suitable and unsuitable candidate genes, respectively. The obtained findings are helpful for future studies on the gene expression in R. officinalis so as to attain improved and reliable results.